(untitled) (Research, Society and Development, 2022)
The present study aims to analyses the pharmaceutical interventions in the identification and prevention of problems related to pharmacotherapy. This study has a quantitative, transversal and descriptive approach. Data were obtained in the period from January to November 2021. All patients admitted to a University Hospital in Sergipe, within the period described above, who required pharmaceutical intervention, were included in this study. Therefore, the variables of interest analyzed were divided into three axes: I) patient data: a) age, b) sex and c) comorbidities; II) problems related to detected drugs and III) pharmaceutical interventions carried out and their acceptability. After collection, data were recorded separately in Microsoft Excel® spreadsheets and analyzed using central tendency techniques. The population studied comprised 357 patients, the majority being male (53%; n=191), with at least one comorbidity, mostly hypertension (48.4%; n=205), diabetes (27%; n=115) and dyslipidemia (6%; n=26). Most interventions (64%; n=325) were accepted and most of these were related to dose adjustment, missing medication, need for additional medication and route of administration. Of the pharmaceutical interventions that were not accepted, it was observed that 26% (n=129) of prescribers did not justify it and 10% (n=52) did it. In view of the results presented, it can be seen that most pharmaceutical interventions were accepted, which may be related to the advancement of understanding of the role of the clinical pharmacist in the health team. These changes bring benefits in clinical outcomes and pharmacoeconomics parameters, since the performance of the multidisciplinary team aims to promote adequate and safe pharmacotherapy for the patient, through the prevention of drug-related problems as well as their rational use.